Adopting PROs in virtual and outpatient management of RA - Taylor, PC (Nature Research, 2020)
The COVID-19 pandemic has catalysed the sudden adoption of telemedicine in the management of rheumatic diseases. In this abrupt transition from in-person visits to telemedicine, can patient-reported outcomes (PROs) help ensure that we continue to achieve optimum disease control and address the concerns of people living with rheumatoid arthritis?